KOMBINASI DAN KOMPOSISI BAHAN BAKU UNTUK PENINGKATAN KUALITAS PAVING RUMPUT DI CV. X SURABAYA - Soejanto, Irwan (JURNAL TEKMAPRO, 2006)
As a product, grass paving has its own characteristic. The producers always try to keep the quality of their product to satisfy their consumers. This research tries to identify some factors that determine pressure strength of grass paving and some dominant factors generate optimum pressure strength and to recommend the ideal material composition to produce a good grass paving. The research shows    portland cement composition (A), water (B), sand (C), and ash (D) determine the pressure strength of grass paving. The combination   level factor:  2.7 kg portland cement , 0.9 lt water , 1.0 kg sand , and 2.0 kg ash  generate optimum pressure strength of grass paving. The SN ratio is derived from  2.7 kg portland cement , 0.9 lt water , interaction  between 2.7 kg portland cement  with 1.4 kg sand , and interaction between  2.7 kg portland cement with  1.0 kg sand. Keywords: Taguchi method, pressure strength, grass paving.